From an antagonistic to a synergistic predator prey perspective : bifurcations in marine ecosystems - Johannessen, Tore; ScienceDirect eBooks (London : Academic Press, 2014)
From an Antagonistic to a Synergistic Predator Prey Perspective: Bifurcations in Marine Ecosystems is a groundbreaking reference that challenges the widespread perception that predators generally have a negative impact on the abundance of their prey, and it proposes a novel paradigm - Predator-prey Synergism - in which both predator and prey enhance abundance by their co-existence. Using this model, the text explains a number of issues that appear paradoxical in the case of a negative predator-prey relationship, including observed ecosystem bifurcations (regime shifts), ecosystem resilience, red tides in apparently nutrient depleted water, and the dominance of grazed phytoplankton over non-grazed species under high grazing pressure. This novel paradigm can also be used to predict the potential impact of global warming on marine ecosystems, identify how marine ecosystem may respond to gradual environmental changes, and develop possible measures to mitigate the negative impact of increasing temperature in marine ecosystems. This book approaches the long-standing question of what generates recruitment variability in marine fishes and invertebrates in an engaging and unique way that students and researchers in marine ecosystems will understand. Introduces a new paradigm, Predator-prey Synergism, as a building block on which to construct new ecological theories. It suggests that Predator-prey Synergism is important in some terrestrial ecosystems and is in agreement with the punctuated equilibria theory of evolution (i.e., stepwise evolution). Suggests a general solution to the recruitment puzzle in marine organisms. Proposes a holistic hypothesis for marine spring blooming ecosystems by considering variability enhancing and variability dampening processes. Asserts that fisheries will induce variability in marine ecosystems and alter the energy flow patterns in predictable ways.
4 Growth and Mortality in Settled Atlantic Cod in Relation to Diet-Evidence for a Recruitment Mechanism4.1 Introduction; 4.1.1 Empirical Background; 4.1.2 Fish Recruitment; 4.1.3 Field Test of a Recruitment Hypothesis for Cod; 4.2 Methods; 4.2.1 Sampling; 4.2.2 Diet and Condition; 4.2.3 Statistical Analyses; 4.3 Results; 4.3.1 Abundance, Size at Settlement, and Growth in 0-Group Cod; 4.3.2 Abundance of Other Littoral Fishes and Prawns; 4.3.3 Diet and Condition in Settled Cod; 4.3.3.1 Diet-July; 4.3.3.2 Condition-July; 4.3.3.3 Location 95-July 1996.
Includes bibliographical references at the end of each chapters and index.
Online resource; title from PDF title page (ScienceDirect, viewed Mar. 20, 2014).
Print version record.
Elsevier
Keywords: Marine ecology; Marine animals -- Effect of predation on; Predatory marine animals; NATURE -- Ecology; NATURE -- Ecosystems & Habitats -- Wilderness; SCIENCE -- Environmental Science; SCIENCE -- Life Sciences -- Ecology; Electronic books